Team perceived virtuality: an emergent state perspective - Handke, L.; Costa, P.; Klonek, F. E.; O'Neill, T. A.; Parker, S. K. (European Journal of Work and Organizational Psychology, 2021)
The rapid changes of work, the ease of mobility, and ubiquitous use of virtual tools have fundamentally changed the way that teamwork in modern organizations is accomplished. Although these developments have elicited a broad range of studies focusing on the phenomenon of team virtuality, the construct itself is still tied to conceptual ambiguities, opposing theoretical underpinnings, and inconsistent findings. The present paper synthesizes the structural and social-constructivist elements of team virtuality in order to introduce the novel concept of team perceived virtuality (TPV), embedded within a theoretical model of its team-level emergence. We define TPV as a cognitive-affective team emergent state which is grounded in collectively experienced feelings of distance and perceptions of information deficits. We further describe how TPV emerges as a function of team members’ collectively developed co-constructions and identify antecedents that contribute towards this emergence. By disentangling perceptions from structural properties, the present paper conceptually advances our understanding of team virtuality beyond its structural characteristics. Ultimately, this conceptual work serves as a starting point for future research on team virtuality as a collectively constructed, team-level emergent construct.